ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP PENERBITAN SUKUK KORPORASI DI INDONESIA - Monica Siti Nurlaila; Atu Bagus Wiguna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Islamic finance in Indonesia in recent years has continued to increase, and the issuance of Sukuk dominates the growth of Islamic finance. However, when viewed from the distribution of corporate Sukuk, growth is lower than state Sukuk. One of the causes of the joint development of corporate Sukuk is the changing macroeconomic factors in Indonesia. Therefore, this study aims to analyze the effect of macroeconomic variables, namely inflation (consumer price index); GDP (gross domestic product); JUB (money supply); and exchange rate (exchange rate) on corporate Sukuk in Indonesia from 2015.7-2020.12. This study uses the Error Correction Model analysis method using Eviews-10 software. This study processes data monthly in the order of July 2015 to October 2020. The results of this study indicate that inflation has a negative and significant effect on the issuance of corporate Sukuk. Gross Domestic Product (GDP) and Total Money Supply (JUB), in a broad sense (M2), have a positive and significant effect. Meanwhile, the exchange rate in this study does not affect the issuance of corporate Sukuk in Indonesia.